Investigating Language-related Tasks in EFL Settings in Light of Tele-Collaboration Phenomenon and Sociocultural Theory - Al Khateeb, Ahmed Abddulateef; Alshahrani, Khalid Saeed (International Journal of Emerging Technologies in Learning (iJET), 2019)
Understanding the criteria of telecollaborative tasks are essential to boost learners’ linguistic, communicative and intercultural competence. This research aims to identify the correlational effect of gender and region on the recognition of the concept of telecollaboration in the sociocultural context of Saudi Arabia. It also focuses on determining and assessing aspects of the criteria of telecollaborative tasks currently employed language learning settings. One hundred and fifty-five teachers of English as a foreign language (EFL) have randomly participated in this study. It was reported that gender and region have no effect on the practice of telecollaboration. The findings have shown that current language learning tasks match some aspects of the criteria of telecollaborative tasks, such as focusing on meaning, negotiation and being reflection-oriented. Finally, this research has contributed to the assessment of the current sittings of EFL settings and to identifying the extent to which current EFL classes meet telecollaboration requirements.